Biomass pyrolysis TGA assessment with an international round robin. (15th September 2020) - Anca-Couce, Andrés; Tsekos, Christos; Retschitzegger, Stefan; Zimbardi, Francesco; Funke, Axel; Banks, Scott; Kraia, Tzouliana; Marques, Paula; Scharler, Robert; de Jong, Wiebren; Kienzl, Norbert
Highlights: Round robin with 7 partners for TGA of cellulose and beech wood pyrolysis. Broad range of values reported in literature for activation energies in pyrolysis TGA. Recommended method to reduce variability and increase reliability of derived kinetics. Complementary use of isoconversional and model fitting methods for reliable kinetics. Abstract: The large variations found in literature for the activation energy values of main biomass compounds (cellulose, hemicellulose and lignin) in pyrolysis TGA raise concerns regarding the reliability of both the experimental and the modelling side of the performed works. In this work, an international round robin has been conducted by 7 partners who performed TGA pyrolysis experiments of pure cellulose and beech wood at several heating rates. Deviations of around 20 – 30 kJ/mol were obtained in the activation energies of cellulose, hemicellulose and conversions up to 0.9 with beech wood when considering all experiments. The following method was employed to derive reliable kinetics: to first ensure that pure cellulose pyrolysis experiments from literature can be accurately reproduced, and then to conduct experiments at different heating rates and evaluate them with isoconversional methods to detect experiments that are outliers and to validate the reliability of the derived kinetics and employed reaction models with a fitting routine. The deviations in the activation energy values for the cases that followed this method, after disregarding other cases, were of 10 kJ/mol or lower, except for lignin and very high conversions. This method is therefore proposed in order to improve the consistency of data acquisition and kinetic analysis of TGA for biomass pyrolysis in literature, reducing the reported variability.